A comparative study of greywater from domestic and public buildings - Cristina Santos (2014)
Greywater (GW) can be an important resource for urban water consumption, replacing potable waterfor purposes that do not require drinking water quality. If applied on a large scale, this practice willreduce the potable water demand and the wastewater produced in urban areas, minimizing thenegative impacts and costs of water extraction and wastewater treatment. A correct characterizationof GW is important to assess its potential for a direct reuse or, if not possible, to make a correctdefinition of a feasible and cost-effective treatment system. This article aims to contribute to thecharacterization of GW produced in washbasins and showers in domestic and public buildings. Acompilation of several works on GW collection and sampling produced by the authors is presented.Samples were taken from GW produced in showers and washbasins in households, changing roomsand in a restaurant. Results are compared with values presented in similar studies and comparedwith standards and guidelines published in different countries.